2020
DOI: 10.1111/1365-2435.13687
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting biomass allocation responses across ontogeny and stress gradients reveal plant adaptations to drought and cold

Abstract: 1. How plants allocate their biomass to different organs is essential to understanding plant adaptations and distributions. Overall, biomass allocation may follow fixed rules across taxa. They are also likely to exhibit substantial departure from these rules during ontogeny and in response to particular limiting factors to optimize their growth and maximize their survival. However, how plants adjust their allocation priorities depending on size and age across stress gradients remain largely unknown in wild pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Allocation to stem and leaf did not vary significantly between the WW and WS treatments, in line with the study conducted by Samanhudi et al (2017) on Rauvolfia serpentina. As to the total biomass, our result generally conforms with the findings reported in many studies, which reported significant tradeoffs among leaves, stems, and roots biomass as influenced by water stress (e.g., Dolezal et al 2020;Li et al 2020;Zhang et al 2015). However, we found a contrasting result on root biomass allocation.…”
Section: Effects Of Water Stress On the Morpho-physiological Traits O...supporting
confidence: 91%
“…Allocation to stem and leaf did not vary significantly between the WW and WS treatments, in line with the study conducted by Samanhudi et al (2017) on Rauvolfia serpentina. As to the total biomass, our result generally conforms with the findings reported in many studies, which reported significant tradeoffs among leaves, stems, and roots biomass as influenced by water stress (e.g., Dolezal et al 2020;Li et al 2020;Zhang et al 2015). However, we found a contrasting result on root biomass allocation.…”
Section: Effects Of Water Stress On the Morpho-physiological Traits O...supporting
confidence: 91%
“…Very early root development is indeed a good indicator of soil phytotoxicity and is used in bioassay studies 44 . The distinction between allometric and plastic biomass partitioning is an important question in the ecological literature to understand plant adaptation to different ecological stresses 45 . Overall, our results confirmed that this essential distinction is valid in polluted environments.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum value of 10 was selected as a reasonable upper bound on temperate deciduous and evergreen forests in our study region. By comparison, the global maximum of MODIS LAI estimates is between 6 and 7, depending on collection (with most values less than 5; Fang et al, 2012;Yan et al, 2016). A global database of field LAI measurements (Iio et al, 2014) contains values as high as 23.5 for evergreen conifer trees and 12.1 for deciduous broadleaf trees, but these are extreme values, and our maximum of 10 is at least 3 standard deviations away from the mean value for evergreen conifer and deciduous broadleaf trees.…”
Section: Model Calibrationmentioning
confidence: 94%